Testing the Effectiveness of Biological Agents as Biofertilizers on the Growth of Two Rice Varieties (Oryza sativa L.) in Screen House - Gibran, Rizki Nabil; Nursandi, Fatimah; Zakia, Aulia (Universitas Muhammadiyah Malang, 2021)
Rice (Oryza sativa L.) is one of the most important food commodities for human nutritional needs. The amount of rice consumption per capita per week in 2017 was 1,571 (BPS, 2018). Population growth over time has resulted in increased demand for rice in Indonesia. Therefore, the demand for rice by the Indonesian people is very high. The problem is that the demand for local rice in Indonesia is still low, so one way to meet the demand for rice in Indonesia is through imports. Utilization of water and land resources is one of the common challenges faced in realizing national food security (Fita et al., 2013). Low productivity of rice plants is generally caused by biological, physical, and chemical soil problems. One of the efforts to increase the productivity of rice plants is by utilizing biological resources such as biofertilizers.The objectives of this study were to determine the appropriate dose of biofertilizer that will affect the growth of rice plants, determine the combination of biofertilizer and application interval that affects the growth of rice plants, and determine the effect of biofertilizer application on 2 varieties of rice plants (Ciherang and IR 64). The design used in this study was a factorial complete randomized block design (RKLT) to determine the interaction and effect of each factor. Then DMRT (Duncan's test) was conducted to determine the best treatment. Based on the results of the study, it was found that the interaction between biofertilizer treatment and rice varieties had significant effects on almost all observed variables except stem diameter at 70 HST, number of clumps at 42 HST, number of productive tillers, and weight of planted seeds. The combination of biofertilizer treatment and rice variety had inconsistent effects on growth parameters and rice yield.